From own-account worker to job creator - Congregado, Emilio; Millán, José María; Román, Concepción (Senate Hall, 2010)
This study aims to increase our understanding of the contribution of the self-employed to the job creation process by investigating the individual decision of hiring employees. Our framework considers the individual decision of becoming self-employed with employees from own account self-employment, while other labour options such as paid employment, unemployment or inactivity are also considered. To this end, we apply multinomial logit models to data from the European Community Household Panel for the EU-15. The results suggest that informal processes for the acquisition of human capital (i.e., previous experience in the labour market or intergenerational transfers) present stronger effects on the decision of hiring employees than do the processes associated with formal education. In addition, we find that business earnings and economic growth have a strong positive effect on the likelihood of recruiting personnel, which supports the prosperity-pull argument. Finally, we also detect international divergences in this decision, which suggest the presence of specific regional factors at the institutional and/or cultural levels. JEL CLASSIFICATION: J23, J24, J38, L26. Keywords: entrepreneurship, own-account workers, employers, job creation, occupational choice, Europe
Keywords: entrepreneurship|own-account workers|employers|job creation|occupational choice|Europe